2021
DOI: 10.3389/fimmu.2021.595811
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Interferon Signaling and Shared Aberrant Basaloid Cells in Single-Cell Profiling of Idiopathic Pulmonary Fibrosis and Systemic Sclerosis-Associated Interstitial Lung Disease

Abstract: Idiopathic pulmonary fibrosis (IPF) and systemic sclerosis-associated interstitial lung disease (SSc-ILD) differ in the predominant demographics and identified genetic risk alleles of effected patients, however both diseases frequently progress to respiratory failure and death. Contrasting advanced SSc-ILD to IPF provides insight to the role dysregulated immunity may play in pulmonary fibrosis. To analyze cell-type specific transcriptome commonalities and differences between IPF and SSc-ILD, we compared single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 69 publications
2
58
0
Order By: Relevance
“…In a recent study performed in IPF and SSc-ILD lung tissues, p16 was predominantly localized to bronchiolized epithelium lining honeycomb cysts, specifically to KRT17 + basal epithelial cells that also coexpress KRT5 + (14). This finding is different from the reported by other authors (2,27,63), which found senescence markers in KRT5 -/KRT17 + epithelial cells, supporting the difficulty to identify with precision the senescent epithelial cells in fibrotic lungs.…”
Section: The Usual Interstitial Pneumonia (Uip) Patternmentioning
confidence: 58%
See 1 more Smart Citation
“…In a recent study performed in IPF and SSc-ILD lung tissues, p16 was predominantly localized to bronchiolized epithelium lining honeycomb cysts, specifically to KRT17 + basal epithelial cells that also coexpress KRT5 + (14). This finding is different from the reported by other authors (2,27,63), which found senescence markers in KRT5 -/KRT17 + epithelial cells, supporting the difficulty to identify with precision the senescent epithelial cells in fibrotic lungs.…”
Section: The Usual Interstitial Pneumonia (Uip) Patternmentioning
confidence: 58%
“…More recently, the presence of KRT5 − /KRT17 + epithelial cells was confirmed in SSc-ILD, where they exhibit markers of EMT, elevated integrin αVβ6, a potent activator of latent TGF-β, and markers of cellular senescence including CDKN2A(p16), CDKN1A(p21) (63).…”
Section: The Elusive Plasticity Of Epithelial Cells In Pulmonary Fibrosismentioning
confidence: 89%
“…More recently, one single-cell RNA-seq cohort identified aberrant basaloid cells in IPF that co-expressed basal epithelial (TP63, KRT17, LAMB3, and LAMC2), mesenchymal (VIM, CDH2, FN1, COL1A1, TNC, and HMGA2), and senescence (CDKN1A, CDKN2A, CCND1, CCND2, MDM2, and GDF15) signature genes [87]. Another study also described aberrant basaloid cells in IPF and systemic sclerosis-related ILDs whereby those cells expressed senescence markers, CDKN2A(gene for p16), CDKN1A(gene for p21), and GDF15 [88], and that cellular senescence was one of the profibrotic regulatory pathways identified in these cells. The new report of "transitional stem cells" or Krt 8 + alveolar differentiation intermediate cells displayed senescent phenotype.…”
Section: Basal Cellsmentioning
confidence: 92%
“…More recently, one single-cell RNA-seq cohort identified aberrant basaloid cells in IPF that co-expressed basal epithelial (TP63, KRT17, LAMB3, and LAMC2), mesenchymal (VIM, CDH2, FN1, COL1A1, TNC, and HMGA2), and senescence (CDKN1A, CDKN2A, CCND1, CCND2, MDM2, and GDF15) signature genes [85]. Another study also described aberrant basaloid cells in IPF and systemic sclerosis-related ILDs, whereby those cells expressed senescence markers, CDKN2A (gene for p16), CDKN1A (gene for p21), and GDF15 [86], and that cellular senescence was one of the profibrotic regulatory pathways identified in these cells. The new report of "transitional stem cells" or Krt 8 + alveolar differentiation intermediate cells displayed a senescent phenotype.…”
Section: Basal Cellsmentioning
confidence: 93%